Modification of cyclic NGR tumor neovasculature-homing motif sequence to human plasminogen kringle 5 improves inhibition of tumor growth. - Weiwei Jiang; Guanghui Jin; Dingyuan Ma; Feng Wang; Tong Fu; Xiao Chen; Xiwen Chen; Kunzhi Jia; Faiz M M T Marikar; Zichun Hua (PLoS ONE, 2012)
BACKGROUND: Blood vessels in tumors express higher level of aminopeptidase N (APN) than normal tissues. Evidence suggests that the CNGRC motif is an APN ligand which targets tumor vasculature. Increased expression of APN in tumor vascular endothelium, therefore, offers an opportunity for targeted delivery of NGR peptide-linked drugs to tumors. METHODS/PRINCIPAL FINDINGS: To determine whether an additional cyclic CNGRC sequence could improve endothelial cell homing and antitumor effect, human plasminogen kringle 5 (hPK5) was modified genetically to introduce a CNGRC motif (NGR-hPK5) and was subsequently expressed in yeast. The biological activity of NGR-hPK5 was assessed and compared with that of wild-type hPK5, in vitro and in vivo. NGR-hPK5 showed more potent antiangiogenic activity than wild-type hPK5: the former had a stronger inhibitory effect on proliferation, migration and cord formation of vascular endothelial cells, and produced a stronger antiangiogenic response in the CAM assay. To evaluate the tumor-targeting ability, both wild-type hPK5 and NGR-hPK5 were (99 m)Tc-labeled, for tracking biodistribution in the in vivo tumor model. By planar imaging and biodistribution analyses of major organs, NGR-hPK5 was found localized to tumor tissues at a higher level than wild-type hPK5 (approximately 3-fold). Finally, the effects of wild-type hPK5 and NGR-modified hPK5 on tumor growth were investigated in two tumor model systems. NGR modification improved tumor localization and, as a consequence, effectively inhibited the growth of mouse Lewis lung carcinoma (LLC) and human colorectal adenocarcinoma (Colo 205) cells in tumor-bearing mice. CONCLUSIONS/SIGNIFICANCE: These studies indicated that the addition of an APN targeting peptide NGR sequence could improve the ability of hPK5 to inhibit angiogenesis and tumor growth.